Weighted sieves with switching - Matomäki, Kaisa; Zuniga-Alterman, Sebastian (Cambridge University Press (CUP), 2025)
Weighted sieves are used to detect numbers with at most S prime factors with  S∈N as small as possible. When one studies problems with two variables in somewhat symmetric roles (such as Chen primes, that is primes p such that  p+2 has at most two prime factors), one can utilise the switching principle. Here we discuss how different sieve weights work in such a situation, concentrating in particular on detecting a prime along with a product of at most three primes.
As applications, we improve on the works of Yang and Harman concerning Diophantine approximation with a prime and an almost prime, and prove that, in general, one can find a pair  (p,P3) when both the original and the switched problem have level of distribution at least  0.267